Fungal Basidiomycete Ceratobasidium theobromae DNA obtained directly from cocoa petioles - Muhammad Junaid; David Guest; AGUS PURWANTARA (Society for Indonesian Biodiversity, 2021)
Abstract. Junaid M, Purwantara A, Guest G. 2021. Fungal Basidiomycete Ceratobasidium theobromae DNA obtained directly from cocoa petioles. Biodiversitas 22: 2838-2843. Understanding the biology of the fastidious Basidiomycete Ceratobasidium theobromae occupying host-tissue is essential for plant disease management. Direct pathogen DNA extraction from infected plant tissue avoids the need for isolation in artificial media. We report a modified DNA isolation protocol to obtain total plant DNA designed to overcome DNA extraction and isolation problems caused by infected petioles rich in polysaccharides and phenolic substances as a primary source of gummosis. This study examined and compared total plant DNA isolated from petioles high in polysaccharides and polyphenolic compounds using two methods: conventional CTAB lysis buffer and Kits (the standard method), and a new modified CTAB protocol to address these PCR inhibitors. The modified method resulted in higher quality and quantity of C. theobromae crude DNA and amplified PCR product. The modified method produced large quantities of clear, transparent, aqueous DNA-containing lysate (crude DNA) with a clear separation between the upper crude DNA and organic waste layers. Mean DNA absorbance was 1.80, and the lowest DNA yield was 836.6 ng/µl. With the standard method, the blurred, viscous lysate obtained showed signs of gummosis, with poor separation between layers of crude DNA, polysaccharides, protein, and organic waste layers and low yield. Gel electrophoresis indicated poor quality DNA extract. We conclude that this modified method will be valuable for genetic diversity and disease studies in a range of previously challenging plant tissues and their pathogens.